PERISTILAHAN DALAM PERNIKAHAN ADAT SUKU DAYAK TAMAN KAPUAS KABUPATEN KAPUAS HULU - Silvester Gerry Jones; Sisilya Saman Madeten; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractResearch on the terms of the Traditional Marriage of Dayak Taman Kapuas as a formof preservation in the importance of preserving the culture and traditions of theancestors. This research aims to describe terms, forms of lingual units and culturalmeanings in the traditional wedding of the Dayak Taman Kapuas in Ingko 'TambeVillage, Kapuas Hulu Regency. The method used in this type of qualitative researchincludes three methods, namely the method of observation, interviews, and descriptivemethods. The techniques of collecting data with fishing, skillful, note taking andtechnique of recording. Based on the research, it was found that the terms premaritalinclude mananya 'and paloa', as well as terms in the marriage procession or sule'which include sijaratan, pasidudukang, patindo', malalangi, malola ', marabut, sala'ason. Then the research also obtained lingual units in the form of words and phrasesand 14 cultural meanings contained in the terms used in the prenuptial procession tomarriage in the custom of the Taman Kapuas Dayak tribe.Keywords: Taman Kapuas Dayak Tribe, Terminology, Traditional Marriage